Politics and society in Reformation Europe : essays for Sir Geoffrey Elton on his sixty-fifth birthday - Kouri, E.I.; Scott, Tom (Basingstoke : Macmillan Press, 1987)
Bibliotheek François Vercammen
Engels
Monografie